A cost–benefit evaluation of direct seeding with and without protector for two native tree species in a tropical rainforest. Issue 2 (5th August 2018) - Prieto‐Rodao, Elena; Ricker, Martin; Siebe, Christina
Abstract : A priority in restoration research is to seek methods that reach high levels of plant establishment at the lowest possible cost. Here, we test how direct seeding works with and without a plastic protector that covers seeds and seedlings in an early‐successional rainforest in Veracruz (Mexico). Two native species, Calophyllum brasiliense (barí) and Vochysia guatemalensis (corpo), at three topographic positions, were used. Germination rates with and without the protector were 84 versus 79% for C. brasiliense, and 98 versus 89% for V. guatemalensis, respectively. The protector significantly improved the germination only of V. guatemalensis . Plant survivorship of V. guatemalensis 27 months after seeding was significantly higher with the protector (78%) than without it (46%). For C. brasiliense, there were no differences in survivorship after 22 months with (61%) and without (54%) protector. In both species, the protector had no effect on height growth, which was significantly larger for seedlings located at the toeslope position. We developed a cost–benefit model that provides a threshold value at which the investment for protectors is justified by a resulting higher survivorship: If 27 months after seeding a treelet of V. guatemalensis is worth at least 0.83 USD on our sites, then the effect of the protector is worth the cost of its implementation (for C. brasiliense, survivorship was statistically undistinguishable with and without protector). We suggest that direct seeding with a plastic protector could be a promising alternative for forest restoration with suitable tree species.